Sustainability or Greenwashing: Evidence from the Asset Market for Industrial Pollution - DUCHIN, RAN; GAO, JANET; XU, QIPING (Journal of Finance, 2025)
ABSTRACT We study the asset market for pollutive plants. Firms divest pollutive plants in response to environmental pressures. Buyers are firms facing weaker environmental pressures that have supply chain relationships or joint ventures with the sellers. While pollution levels do not decline following divestitures, sellers highlight their sustainable policies in subsequent conference calls, earn higher returns as they sell more pollutive plants, and benefit from higher Environmental, Social, and Governance (ESG) ratings and lower compliance costs. Overall, the asset market allows firms to redraw their boundaries in a manner perceived as environmentally friendly without real consequences for pollution but with substantial gains from trade.